Estudio de prefactibilidad para la instalación de una planta de producción de macerado de pisco con maca (Lepidium meyenii) y maracuyá (Passiflora edulis) - Córdova Pérez, María Celeste (2020)
In this project, the prefeasibility to install a pisco macerate production plant with maca and passion fruit was determined, demonstrating its market, technological, economic, social and environmental viability. The market study estimated a demand in the fifth year of 50,659 bottles. The target market is made up of people from Metropolitan Lima (25-55 years old), from the NSE "B" and "C" sectors. For said socioeconomic segmentation, life styles and their characteristics will be taken into account. In the analysis of the location of the plant, the best location was determined in the district of Lurín according to the criteria of proximity to the market, cost of the land, proximity of the raw material, among others. On the other hand, the maximum plant size is determined by the market and the minimum by the equilibrium point with 22,365 bottles. The plant capacity is limited by the Macerado operation, this activity being the bottleneck. The production program was established following the inventory method, giving a monthly production of 3,376 bottles in the first year. In addition, as a result of the analysis of the plant layout, it was obtained that the area will be 397.5 m². Regarding the economic and financial evaluation, it was determined that the total investment is S / 828 986.56. Being the most profitable to request bank financing of 40% of the total investment, as it returns a NPV of S / 478 566.55 in 5 years and an IRR of 39.61%. Likewise, the recovery period would be 3.54 years and 1.96 soles of profit were needed for each sol invested. Finally, in the Social Evaluation through the indicators it was concluded that the Added Value of the Project is S / 1 498 229,24, the Capital Intensity is 0.33 times, the product-capital ratio is 3.01 and the Capital Density resulted in S / 55,265.77 per job.